2020
DOI: 10.1002/ange.202004994
|View full text |Cite
|
Sign up to set email alerts
|

Protein and mRNA Delivery Enabled by Cholesteryl‐Based Biodegradable Lipidoid Nanoparticles

Abstract: Developing safe and efficient delivery systems for therapeutic biomacromolecules is a long‐standing challenge. Herein, we report a newly developed combinatorial library of cholesteryl‐based disulfide bond‐containing biodegradable cationic lipidoid nanoparticles. We have identified a subset of this library which is effective for protein and mRNA delivery in vitro and in vivo. These lipidoids showed comparable transfection efficacies but much lower cytotoxicities compared to the Lpf2k in vitro. In vivo studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Recently, Xu's group designed a series of bioreducible lipidoids for Cas9 mRNA/sgRNA delivery. [191][192][193][194] For example, BAMEA-O16B, one of the leading lipids, formulated with the helper lipids, DSPE-PEG2000 and Cas9 mRNA/ sgPCSK9 could reduce PCSK9 protein levels in mouse serum to…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Xu's group designed a series of bioreducible lipidoids for Cas9 mRNA/sgRNA delivery. [191][192][193][194] For example, BAMEA-O16B, one of the leading lipids, formulated with the helper lipids, DSPE-PEG2000 and Cas9 mRNA/ sgPCSK9 could reduce PCSK9 protein levels in mouse serum to…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…The same group also reported a new class of cholesteryl-based bioreducible lipidoids as well as another type that showed effective Cas9 mRNA delivery to human mesenchymal stem cells (hMSCs). 192,194 As an alternative to disulfide bond-containing bioreducible lipids, Zhang et al designed a series of lipid-like compounds containing ester groups for Cas9 mRNA delivery. 195 The study showed that linear ester chains were degraded much faster than branched ester chains and both types demonstrated efficient Cas9 mRNA delivery in vitro and in vivo.…”
Section: Reviewmentioning
confidence: 99%
“…To further expand the library of biodegradable lipids, we further incorporated novel head groups (imidazole and its analogs) 41 and tails (cholesteryl-based and cyclic benzylidene acetal-containing tails) 42 , 43 into the lipid molecule design. Our studies found that these newly developed lipid materials are safe and efficient carriers for the intracellular delivery of mRNA, both in vitro and in vivo in mouse models.…”
Section: Lnps For the Delivery Of Nucleic Acidsmentioning
confidence: 99%
“…Even though we and others have shown that by altering the lipid chemistry and LNP formulation composition, certain properties ( e.g. , increase cell and tissue specificity, augmented intracellular transfection efficacy, triggered degradability, improved biocompatibility and reduced toxicity, increased membrane fluidity, and enhanced storage stability) could be introduced to the LNP system, a thorough lipid structure‒activity study is needed to fully understand how the LNP systems interact with biological systems both in cell culture and in vivo 31 , 36 , 37 , 42 , 112 . It is critical to understand how the combinatorial lipids with different head, linker, and tail groups and LNPs with different size, morphology, surface chemistry, and charge properties result in differences in cell transfection efficacy, cytotoxicity, and in vivo biodistribution profiles 124 , 125 , 126 , 127 , 128 .…”
Section: Challenges and Future Studiesmentioning
confidence: 99%
“…Onpattro was the first FDA-approved siRNA-LNP drug for the treatment of polyneuropathies caused by hereditary transthyretin amyloidosis (5). LNPs have been extensively studied for the delivery of large molecules like polypeptides and nucleic acids (6)(7)(8)(9)(10)(11), however, their delivery potential for small molecule drugs remains unexplored. We propose that delivery of adenosine triphosphate (ATP) to the brain endothelial cells (BECs) lining the blood-brain barrier (BBB) is an effective strategy to increase the cell viability of BECs post-cerebral ischemia/reperfusion injury (stroke).…”
Section: Introductionmentioning
confidence: 99%